Cyclins and CDKs in the regulation of meiosis-specific events - Palacios-Blanco, Inés; Martín-Castellanos, Cristina (Frontiers in Cell and Developmental Biology, 2022)
How eukaryotic cells control their duplication is a fascinating example of how a biological system self-organizes specific activities to temporally order cellular events. During cell cycle progression, the cellular level of CDK (Cyclin-Dependent Kinase) activity temporally orders the different cell cycle phases, ensuring that DNA replication occurs prior to segregation into two daughter cells. CDK activity requires the binding of a regulatory subunit (cyclin) to the core kinase, and both CDKs and cyclins are well conserved throughout evolution from yeast to humans. As key regulators, they coordinate cell cycle progression with metabolism, DNA damage, and cell differentiation. In meiosis, the special cell division that ensures the transmission of genetic information from one generation to the next, cyclins and CDKs have acquired novel functions to coordinate meiosis-specific events such as chromosome architecture, recombination and synapsis. Interestingly, meiosis-specific cyclins and CDKs are common in evolution, some cyclins seem to have evolved to acquire CDK-independent functions, and even some CDKs associate with a non-cyclin partner. We will review the functions of these key regulators in meiosis where variation has specially flourished.